Methodological Difficulties of Conducting Agroecological Studies from a Statistical Perspective - Bianconi, Andre [UNESP]; Dalgaard, Tommy; Manly, Bryan F. J.; Govone, Jose S. [UNESP]; Watts, Michael J.; Nkala, Peter; Habermann, Gustavo [UNESP]; Huang, Yanbo; Serapiao, Adriane B. S. [UNESP] (Taylor & Francis Inc, 2013)
Statistical methods for analyzing agroecological data might not be able to help agroecologists to solve all of the current problems concerning crop and animal husbandry, but such methods could well help them assess, tackle, and resolve several agroecological issues in a more reliable and accurate manner. Therefore, our goal in this article is to discuss the importance of statistical tools for alternative agronomic approaches, because alternative approaches, such as organic farming, should not only be promoted by encouraging farmers to deploy agroecological techniques, but also by providing agroecologists with robust analyses based on rigorous statistical procedures.
Keywords: agroecology; multivariate statistics; scale of farming; sample size; ecological agriculture